Development and validation of pre-assessment tools in grade 7 physics - Rieza, Edwin A., Jr. (Animo Repository, 2018)
The primary purpose of the study was to develop pre-assessment tools in Grade 7 Physics that will determine students prior knowledge and readiness. The test development started first with the identification of students existing alternative conceptions through the use of a self developed Three-tier test. The identified alternative conceptions of Grade 7 students were listed and included in two multiple-choice tests - Physics Skills Test (PST) and Physics Knowledge Test (PKT). PST comprises of related learning competencies from Grade 3 to Grade 7 Physics (54 items), while PKT contains learning competencies for Grade 7 only (60 items). These two pilot tests were administered to two sections of Grade 6 students (N=85). After the item analysis, the final form of the test was made containing 30 items each for PST and PKT. The final form of the tests were administered to Grade 7 students from Religious of the Virgin Mary (RVM) Schools in Luzon (N = 988). Descriptive statistics showed that PST has an acceptable reliability coefficient (M = 14; SD = 4.61; a = 0.67) and approaching normal distribution (Skewness = 0.16; Ku = - 0.53). Furthermore, it has average difficulty index of 0.49 and discrimination index of 0.32 (Good). PKT has low reliability coefficient ( M = 12 ;SD = 4.02 ;a = 0.57 ) and approaching normal distribution (Skewness = 0.21; Ku = -0.39). Moreover, it has average difficulty of 0.42 and discrimination index of 0.28 (Marginal). Finally, stanine scores for PST and PKT were computed to determine the profile of the students.